2018
DOI: 10.1200/jgo.18.00018
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Survival Benefits of Metformin in Middle Eastern Patients With Type II Diabetes Mellitus and Colorectal Cancer

Abstract: PurposeEpidemiologic data from several populations suggest that metformin may decrease cancer risk and mortality in patients with colorectal cancer (CRC) and type II diabetes mellitus (DM). Although type II DM and CRC are major health problems in the Middle East, no investigations have been performed to test the effect metformin has on the outcome of patients with type II DM and CRC who are also treated with metformin.Materials and MethodsWe retrospectively reviewed the medical records of 1,902 patients diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
9
0
1
Order By: Relevance
“…Data concerning potential uses of metformin as an adjuvant treatment in patients who have already developed colorectal cancer are even more scarce: while a series of published papers suggest that metformin use might be associated with improved survival [ 85 , 86 , 87 , 88 ], in all these studies, the number of patients with unresected metastatic disease is rather low (usually lower than 3–4% of the whole patient population).…”
Section: Resultsmentioning
confidence: 99%
“…Data concerning potential uses of metformin as an adjuvant treatment in patients who have already developed colorectal cancer are even more scarce: while a series of published papers suggest that metformin use might be associated with improved survival [ 85 , 86 , 87 , 88 ], in all these studies, the number of patients with unresected metastatic disease is rather low (usually lower than 3–4% of the whole patient population).…”
Section: Resultsmentioning
confidence: 99%
“…14,15 Multiple systematic reviews and meta-analyses of observational studies have demonstrated that metformin exposure is associated with reduced cancer risk and prolonged RFS when used concurrently with chemotherapy. 16,17 The current study examines the use of metformin in patients with known colorectal liver metastases who undergo R0 or R1 resection of liver disease. Here, we found a strong association between metformin use and prolonged RFS and OS in patients with CRLM who undergo a hepatic resection that eliminates gross metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…The upper chamber of the Transwell chamber for cell invasion experiments was first uniformly coated with 50 µl of Matrigel, and DMEM containing 10% fetal calf serum was added to the lower chamber of the Transwell chamber. Then, a well-grown SW480 cell suspension was inoculated into the upper chamber of the Transwell chamber, and the inoculated cell density was 1x10 5 . SW480 cells in the upper chamber were placed at 37˚C, in 5% CO 2 cell incubator and cultured with serum-free medium for 24 h. After the completion of the culture, SW480 cells on the surface of the membrane were washed, and the remaining SW480 cells were fixed with 4% paraformaldehyde and stained with 0.1% crystal violet for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that diabetes, especially type 2 diabetes, can increase the risk of cancer and death, especially in gastrointestinal cancers ( 5 ). Type 2 diabetes is an independent risk factor for colon cancer, and colon cancer patients with diabetes have a worse prognosis than those without diabetes ( 6 ).…”
Section: Introductionmentioning
confidence: 99%